2001
DOI: 10.1021/jf001429c
|View full text |Cite
|
Sign up to set email alerts
|

Determination ofN-(Carboxymethyl)fumonisin B1in Corn Products by Liquid Chromatography/Electrospray Ionization–Mass Spectrometry

Abstract: It is well-known that fumonisin B(1) (FB(1)) in corn meal decreases during baking, frying, and cooking, but it is still not exactly clear how heating affects the formation of N-(carboxymethyl)fumonisin B(1) (NCM-FB(1)), the reaction product of FB(1) and reducing sugars. In model experiments corn grits were spiked with FB(1) (2 mg/kg) and D-glucose (50 g/kg) or sucrose (50 g/kg) and manufactured into extrusion products at various temperatures (160--180 degrees C) and moisture levels (16--20%). A liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 27 publications
3
49
0
2
Order By: Relevance
“…While, from a structure-function standpoint, this reaction sequence is intriguing toxicologically (see below), little to no NCM-FB1 or NDF-FB 1 has been found in corn [95,99] or nixtamalization products [95]. At higher temperatures, e. g., under extruding conditions (see Table 2), only low concentrations (27 -97 lg/kg) [81] of NCM-FB 1 were detected in a product made from cornmeal spiked with 2 mg/kg FB 1 .…”
Section: Fumonisin Reaction Products and Matrix Bindingmentioning
confidence: 95%
See 3 more Smart Citations
“…While, from a structure-function standpoint, this reaction sequence is intriguing toxicologically (see below), little to no NCM-FB1 or NDF-FB 1 has been found in corn [95,99] or nixtamalization products [95]. At higher temperatures, e. g., under extruding conditions (see Table 2), only low concentrations (27 -97 lg/kg) [81] of NCM-FB 1 were detected in a product made from cornmeal spiked with 2 mg/kg FB 1 .…”
Section: Fumonisin Reaction Products and Matrix Bindingmentioning
confidence: 95%
“…Both found significant reductions of fumonisin concentration in the extruded product, however, the amount of reduction depended on the type and amount of sugar added. Extruding corn grits that were spiked with 2 mg/kg FB 1 resulted in a 68 -77% reduction of FB 1 with added sucrose and in a 85 -93% reduction of FB 1 with added glucose (parameters see Table 2) [81]. Castelo et al [56] found a fumonisin reduction of 45 -71% when glucose, 30 -53% when fructose and 19 -39% when sucrose was added.…”
Section: Thermal Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The same group also proposed this method for the determination of N-(carboxymethyl)-fumonisin B1 (NCM-FB1), the degradation product formed by reaction of fumonisin B1 with reducing sugars, in corn products (Seefelder, Hartl, & Humpf, 2001). By using D 6 -FB1 as internal standard, they obtained a LOD of 10 ppb by monitoring the protonated ion of NCM-FB1.…”
Section: A Liquid Chromatography/mass Spectrometry Analysis Of Fumonmentioning
confidence: 99%